Frequency and Sensitivity Pattern of Neisseria gonorrhoae Isolated from Women at a Tertiary Care Hospital in Dhaka City - Nusrat, Fatema; Islam, K.M. Shahidul; Shamsuzzaman, S.M.; Yusuf, Md. Abdullah; Farzana, Aleya; Afrin, Samia (Bangladesh Journal of Infectious Diseases, 2015)
Background: Antibiotic sensitivity pattern of Neisseria gonorrhoae is changing frequently. Objective: The purpose of the present study was to see the antibiotic sensitivity pattern of Neisseria gonorrhoae isolated from women presented with cervicitis. Methodology: This cross sectional study.carried out in the Department of Microbiology at Dhaka Medical College, Dhaka from July 2011 to December 2012 for a period of one and half year. All the women presented with or without the clinical features of cervicitis at child bearing age (15 to 49 yrs) with or without pregnancy were enrolled as study population. Endocervical swabs were collected for Gram staining, culture, biochemical test from clinically diagnosed patients of cervicitis for presumptive identification of Neisseria gonorrhoeae. The isolates with presumptive identification were confirmed by rapid carbohydrate utilization test (RCUT), which differentiates N.gonorrhoeae from other Neisseria. Antimicrobial susceptibility test was done according CLSI guideline. Result: A total 245 females were recruited of which N. gonorrhoeae were detected from 39(15.9%) cases. Among 39 positive cases of gonococcal cervicitis, 19 (48.71%) were detected in the age group of 21-30 years. 56.41% were sensitive and 30.76% were resistant to ceftriaxone. Similarly 51.28% were sensitive and 23.07% were resistant to cefuroxime; 23.07% sensitive, 30.76% moderately sensitive and 46.15% resistant to ciprofloxacin. Conclusion: Gonococcal cervicitis is found in a high frequency rate with a reduced sensitivity to antibiotics especially ciprofloxacin, second and third generation cephalosporins. Bangladesh J Infect Dis 2014;1(1):3-7